Improving Heat Transfer of Plate-Fin Heat Sinks Using through Rod Configurations - Abdelmohimen, M.A.H. (American Society of Mechanical Engineers (ASME), 2021)
The performance of the heat sink has been investigated as using rods through its fins. The shear-stress transport k-Ï model is selected to carry out this study. Two different flow directions have been studied. Four cases are represented, including the baseline case which has no rods through the fins. Two, four, and six rods are used through the fins. Thermal resistance, pumping power, and Nusselt number have been represented and discussed through this study. The results show that as the number of rods increases, the thermal resistance decreases while the required pumping power increases. The impinging flow direction shows higher performance as compared with the suction flow direction. As the Reynolds number increases, the Nusselt number increases for all studied cases. The optimum case along with the studied range of Reynolds number and number of rods is case-2 (has four rods through fins). Â© 2020 Georg Thieme Verlag. All rights reserved.